2010
DOI: 10.1001/archinternmed.2009.547
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Hospice Use Among Patients With Heart Failure

Abstract: Background Heart failure is the leading non-cancer hospice diagnosis and the leading cause of hospitalization among Medicare beneficiaries. Racial differences in hospice use are well documented for cancer but poorly described for heart failure. Methods Based on a national sample of 98,258 Medicare beneficiaries aged 66 and older on January 1, 2001 with a diagnosis of heart failure, who were not enrolled in hospice in 2000, we determined the effect of race/ethnicity on hospice entry for heart failure in 2001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 35 publications
4
69
0
Order By: Relevance
“…Moreover, some studies have found that African Americans have higher rates of heart-failurerelated hospitalizations compared with Caucasians (Deswal, Petersen, Urbauer, Wright, & Beyth, 2006;Husaini et al, 2011). Historically African Americans have experienced inequality in the quality of health care they have received, and consequently may distrust the medical system, preferring active treatment over palliative care (Allen, Allen, Hilgeman, & DeCoster, 2008;Braun, Beyth, Ford, & McCullough, 2008;Givens Tjia, Zhou, Emanuel, & Ash, 2010;LaVeist, Nickerson & Bowie, 2000). These factors can have important implications for how African Americans approach medical care, their access to services, and their desire for medical information and treatment (Torke, Corbie-Smith, & Branch, 2004).…”
Section: Notice In Compliance With Publisher Policy: This Is An Authomentioning
confidence: 99%
“…Moreover, some studies have found that African Americans have higher rates of heart-failurerelated hospitalizations compared with Caucasians (Deswal, Petersen, Urbauer, Wright, & Beyth, 2006;Husaini et al, 2011). Historically African Americans have experienced inequality in the quality of health care they have received, and consequently may distrust the medical system, preferring active treatment over palliative care (Allen, Allen, Hilgeman, & DeCoster, 2008;Braun, Beyth, Ford, & McCullough, 2008;Givens Tjia, Zhou, Emanuel, & Ash, 2010;LaVeist, Nickerson & Bowie, 2000). These factors can have important implications for how African Americans approach medical care, their access to services, and their desire for medical information and treatment (Torke, Corbie-Smith, & Branch, 2004).…”
Section: Notice In Compliance With Publisher Policy: This Is An Authomentioning
confidence: 99%
“…Local hospice utilization, previously defined by Givens et al as the proportion of deaths in each HSA that occurred while the patient was enrolled in hospice, reflects regional patterns of hospice utilization. 31 We used data from the years 2005 to 2009 to calculate the local hospice utilization for each HSA, and then grouped the spectrum of values into tertiles representing high, medium, and low hospice utilization areas. We defined 30-day hospice enrollment as the presence of at least one Medicare hospice claim within 30 days after the index hospitalization admission date.…”
Section: Variablesmentioning
confidence: 99%
“…Studies evaluating hospice and palliative care programs have reported improved pain control (Ciemins, Blum, Nunley, Lasher, & Newman, 2007;Elsayem et al, 2004;Hanlon, Perera, Sevick, Rodriguez, & Jaffe, 2010;Miller, Mor, & Teno, 2003), improved patient and family satisfaction with care (Brumley et al, 2007;Dy, Shugarman, Lorenz, Mularski, & Lynn, 2008;Gade et al, 2008;O'Mahoney, Blank, Zallman, & Selwyn, 2005;Teno et al, 2004), and in some cases increased survival rates (Connor, Pyenson, Fitch, Spence, & Iwasaki, 2007). Despite this significant growth, studies have consistently documented the underuse of these services by minorities (for the purpose of this article, minorities refers to both racial and ethnic minorities; EnguĂ­danos, Yip, & Wilber, 2005;Givens, Tjia, Zhou, Emanuel, & Ash, 2010;Greiner, Perera, & Ahluwalia, 2003;Johnson, Kuchibhatla, Tanis, & Tulsky, 2008;Kwak, Haley, & Chiriboga, 2008;Ngo-Metzger, Phillips, & McCarthy, 2008;Smith, Earle, & McCarthy, 2009). While studies have identified several factors contributing to reduced rates of EOL care usage among minorities, research has yet to incorporate the full scope of factors in operation, thus impeding the development of more comprehensive interventions capable of improving minority EOL care access.…”
Section: Introductionmentioning
confidence: 99%